2022
DOI: 10.1007/s15010-022-01915-7
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab vs. baricitinib in hospitalized severe COVID-19 patients: results from a real-world cohort

Abstract: Background Tocilizumab and baricitinib are recommended treatment options for hospitalized COVID-19 patients requiring oxygen support. Literature about its efficacy and safety in a head-to-head comparison is scarce. Methods Hospitalized COVID-19 patients requiring oxygen were treated with tocilizumab or baricitinib additionally to dexamethasone. Tocilizumab was available from February till the 19th of September 2021 and baricitinib from 21st of September. The primary outcome was in-hospital mortality. Secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A network meta-analysis was conducted to assess the efficacy and safety of immunomodulators in patients with COVID-19, revealing that tocilizumab may pose a higher risk of infection compared to baricitinib (Ngamprasertchai et al, 2022). Other studies have additionally indicated an elevation in the incidence of thrombosis or acute liver injury among individuals administered tocilizumab as opposed to baricitinib (Karolyi et al, 2023;Peterson et al, 2023;Reid et al, 2023). Our study found that the tocilizumab group had adverse effects more frequently, including secondary infections, thrombotic events, and acute liver damage.…”
Section: Figurementioning
confidence: 66%
“…A network meta-analysis was conducted to assess the efficacy and safety of immunomodulators in patients with COVID-19, revealing that tocilizumab may pose a higher risk of infection compared to baricitinib (Ngamprasertchai et al, 2022). Other studies have additionally indicated an elevation in the incidence of thrombosis or acute liver injury among individuals administered tocilizumab as opposed to baricitinib (Karolyi et al, 2023;Peterson et al, 2023;Reid et al, 2023). Our study found that the tocilizumab group had adverse effects more frequently, including secondary infections, thrombotic events, and acute liver damage.…”
Section: Figurementioning
confidence: 66%
“…The 28-day mortality rate is only the secondary outcome reported in the overall group and it was shown to be significantly lower in the baricitinib group (tocilizumab 49% vs. baricitinib 39%, p = 0.001). Karolyi et al (2021) showed that, among 159 patients with COVID-19 infection, hospital mortality, progression to MV, and hospital LOS were higher in the tocilizumab group but these results were not statistically significant at, respectively, 18% vs. 11% (p = 0.229), 19% vs. 11% (p = 0.173), and 13 vs. 12 days (p = 0.114) [22]. Two other similar but smaller studies also showed the same finding of no significant mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational cohort studies have indicated that BAR reduces mortality and the risk of progression to invasive mechanical ventilation in hospitalized patients with COVID-19 infection. Moreover, when compared to tocilizumab, BAR has been associated with a lower risk of elevated liver enzyme levels [16][17][18]. The collective randomized evidence available to date indicates that JAK inhibitors, primarily BAR, decrease mortality in patients hospitalized for COVID-19 by approximately one-fth [18].…”
Section: Introductionmentioning
confidence: 99%